Fenomena Cyberbullying Pada Peserta Didik - Elpemi, Nopia; Isro'i, Nurul Faqih (IJoCE: Indonesian Journal of Counseling and Education, 2020)
The development of technology and information goes so fast. There are many types of media used to communicate. But not infrequently the use of these media has a negative impact. One negative effect is cyberbullying behavior. Cyberbullying behavior is very vulnerable experienced by adolescents in this case students. Students who are still in development, puberty, is a transition from childhood to adolescence. At this time adolescents have a high desire in trying new things to find their true identity. By communicating adolescents One way is to formalize with many people both directly and indirectly by using the help of information and communication media technology. In this stage, students need understanding and assistance to prevent cyberbullying. Abstrak Perkembangan teknologi dan informasi berjalan begitu cepat. Banyak sekalai jenis media yang digunakan untuk berkomunikasi. Namun tidak jarang penggunaan media tersebut mempunyai dampak negatif. Salah satu dampak negatifnya adalah perilaku cyberbullying. Perilaku cyberbullying sangat rentan dialami remaja dalam hal ini peserta didik. Peserta didik yang masih dalam masa perkembangan yakni masa pubertas, merupakan peralihan dari masa anak-anak ke masa remaja. Di masa ini remaja mempunyai keinginan yang tinggi dalam mencoba hal-hal baru guna mencari jati dirinya. Dengan berkomunikasi remaja Salah satu caranya adalah bersoisalisasi dengan orang banyak baik secara langsung maupun tidak langsung dengan menggunakan bantuan media teknologi informasi dan komunikasi. Dalam tahap ini peserta didik perlu pemahaman dan pendampingan agar tidak terjadi cyberbullying.